(untitled) (Research, Society and Development, 2024)
Women Urban Solid Waste Collectors (MSW) reinforce the position of leaders that have been constituted through women, seeking the central place within the cultural and historical scenario in which women were placed in the position of supporting actors in society. From this, the study aims to: To analyze the historicity of women solid waste collectors and focusing on the environmental crisis in the municipality of Magalhães Barata/PA. Methodology. This is a narrative literature review of a descriptive nature and a qualitative approach. Results: 15 publications and 5 books on scientific research methodology were used to compose the results, making them eligible by presenting a synthesis of analysis of these results. Final considerations: there is a predominance of 75% of women working as solid waste collectors in associations and cooperatives while they were excluded from formal work, with the stigma of survival in dumps and unhealthy places in search of waste discarded by society and that guarantees family sustenance.